Achieving permanence for older children and youth in foster care - Kerman, Benjamin; Freundlich, Madelyn; Maluccio, Anthony N. (Columbia University Press, 2009)
Through a novel integration of child welfare data, policy analysis, and evidence-informed youth permanency practice, the essays in this volume show how to achieve and sustain family permanence for older children and youth in foster care. Researchers examine what is known about permanency outcomes for youth in foster care, how the existing knowledge base can be applied to improve these outcomes, and the directions that future research should take to strengthen youth permanence practice and policy. Part 1 examines child welfare data concerning reunification, adoption, and relative custody and guardianship and the implications for practice and policy. Part 2 addresses law, regulation, court reform, and resource allocation as vital components in achieving and sustaining family permanence. Contributors examine the impact of policy change created by court reform and propose new federal and state policy directions. Part 3 outlines a range of practices designed to achieve family permanence for youth in foster care: preserving families through community-based services, reunification, adoption, and custody and guardianship arrangements with relatives. As growing numbers of youth continue to "age out" of foster care without permanent families, researchers, practitioners, and policymakers have increasingly focused on developing evidence-informed policies, practices, services and supports to improve outcomes for youth. Edited by leading professionals in the field, this text recommends the most relevant and effective methods for improving family permanency outcomes for older youth in foster care.